EARLY MODERN PRINTERS AND THE STANDARDIZATION OF ENGLISH SPELLING. - Howard-Hill, T. H. (Modern Language Review, 2006)
The article focuses on the mechanism and the evolution of the standardization of English spelling in the context of early modern printers. Compositors brought with them to the printing house their traditional spellings that reflected their regional origins. The question of why these spellings changed at all and became standardized when it was to the benefit of the compositors to follow their copy in successive reprints lies within the ambit of the derivative sense of economy as the thrifty and efficient use of material resources. According to this, one can expect an avoidance of unnecessary or unproductive effort by compositors with a desire for maximum return from labor and materials by master printers. Printers employed their spellings which influenced the readers. The printers then employed them in their writings, although inconsistently at first, and standardized the older spellings of their copies, by then unacceptable. Then they published more books, and so on. Schoolmasters taught the reformed printers' spellings that were printed in their spelling books, grammars, and dictionaries. All such influences, in conjunction with printing and the operations of the printing house, brought about the graphemic, but not phonemic, uniformity which is experienced today.